Kajian Pembuatan MOL (Mikroorganisme Lokal) Spesifik dengan Variasi Jenis dan Konsentrasi Bahan Tambahan - Irfan Irfan; Dewi Yunita; Fitriani Fitriani (Jurnal Teknologi dan Industri Pertanian Indonesia, 2021)
This study aims to determine the effect of type and concentration of additives in production of local microorganisms (MOL) on overall qualities (physical, chemical, sensory, and microbiological). The method used in this study was a factorial completely randomized design (CRD) consisting of two factors. The first factor was the type of additive (J) which consisted of 4 levels, namely rice (J1), soil (J2), leaf bokashi (J3), and leaf compost (J4). The second factor was the concentration of additives (K) which consisted of 2 levels, namely 7.5% (K1) and 10% (K2). The product was analysed total cell counts (TCC), pH, temperature, and organoleptic tests (hedonic test) on color and organoleptic (descriptive test) on aroma. The best MOL was J4K2 (combination between leaf compost and 10%). The J4K2 MOL had the following characteristics: TCC of 9.6x107 CFU / ml, pH value of 3.7, color hedonic test of 4.3 (preferred by panelists) and aroma descriptive test of 4.3 (tape aroma / medium acid).